2008
DOI: 10.2174/092986608784246452
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Novel Peroxidase from Bitter Gourd (Momordica charantia)

Abstract: Peroxidase from bitter gourd was purified by three step purification scheme; ammonium sulphate fractionation, gel filtration and affinity chromatography. The enzyme was purified 42 fold with the retention of 67% of the initial activity. The enzyme exhibited its maximum activity at pH 5.6 and 40 degrees C. The enzyme retained half of its activity even after 1 h incubation at 60 degrees C. Molecular weight of the purified glycosylated bitter gourd peroxidase determined by Sephacryl S-100 and SDS-PAGE was 43 kDa.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…Amongst these, samples made of Resomer L 210 (m) 40 : 60 composites showed the highest diffusion coefficient of 14.05 * 10 −10 m 2 /s due to their rough structured polymer matrix as described earlier. Contrary to the diffusion coefficients published for peroxidase in aqueous solution by Fatima and Husain [41] the measured values inside the diffusion cell were once again ten times higher as observed for glucose diffusion before.…”
Section: Glucose Diffusioncontrasting
confidence: 95%
“…Amongst these, samples made of Resomer L 210 (m) 40 : 60 composites showed the highest diffusion coefficient of 14.05 * 10 −10 m 2 /s due to their rough structured polymer matrix as described earlier. Contrary to the diffusion coefficients published for peroxidase in aqueous solution by Fatima and Husain [41] the measured values inside the diffusion cell were once again ten times higher as observed for glucose diffusion before.…”
Section: Glucose Diffusioncontrasting
confidence: 95%
“…stratiotes leaf peroxidase maintained over 60% of its activity over a temperature range of 30ºC to 50ºC. Although, other studies have reported higher stability, comparison is however quite difficult to make since most studies were carried out with enzyme sample with inconsistent level of purity (Marzouki et al, 2005;Aiman and Quayyum, 2008;Wang et al, 2009;Hu et al, 2012). The difference observed in activities of P. stratiotes leaf peroxidase incubated for 30 and 60 minutes at temperatures below 60˚C ( Figure 5) is related to the rate of denaturation, since denaturation is both time and temperature dependent.…”
Section: Discussionmentioning
confidence: 99%
“…There was almost no activity after day 8 at those pH values. However, there are reports showing that the optimum pH of POD varies; for example, it is pH 5.0 for bitter gourd [35] and pH 7.0 for Raphanus sativus [36] and between pH 5.3-6.3 for wheat germ. [37] Optimum temperature profile and thermal stability For determination of thermal and storage stability, POD activities were measured at different temperatures.…”
Section: Molecular Weight and Puritymentioning
confidence: 99%